The Press of Quebec Through Media Regionalism Prism: From Origin to Digital Epoch (XVIII – the beginning of the XXI century) - Elena F. Ovcharenko (Гуманитарный вектор)
Today all national languages and cultures feel this inconceivable pressing by global English-Language digital world transformation. In addition, we examine second actual problem – information inequality in multinational countries and “answer-reaction” of one national minority. Quebec is the only French-speaking province of Canada. We present agenda of Quebec French-language press during two centuries through Media Regionalism – our specifi c term for reaction of Quebec Francophones constantly surrounded by total English-speaking information environment. Practically, media regionalism is not studied by Russian researchers. Analyzing Quebec French-language press as material we formulate hypothesis of research: media regionalism is its historical feature, which defends successfully cultural and traditional values of Quebec. Key aspect of the present research problem is scientifi c defi nition for media regionalism. For characterization of media regionalism evolution in Quebec we used mainly the methodology of complex analysis. As a result, we should note that media regionalism, on the one hand, defends Quebec identity, but on the other hand, reminds self-censorship of newspapers. Elucidating the questions of French language, Quebec traditions and culture, media regionalism refuses international news, information of other Canadian provinces, etc. Seeing media regionalism as the basis of Quebec information politics during more than two centuries, we can predicate its future great vitality for French-language press. Quebec media regionalism is peculiar defense from external destructive factors – such as transition to British Crown in the XVIIIth century or global digital world transformation in the XXIth. Media regionalism information problem is important for many other multinational countries. Finally, it is necessary to continue these studies.